Analisis Usability Sistem Permohonan Legalisir Menggunakan Metode System Usability Scale - Wahyudi Ariannor; Devia Rahma Safitri; Rustati Rahmi (STMIK Banjarbaru, 2023)
One of the applications of e-Government in the districts is the application for legalization of documents that can be accessed widely. Since it was implemented, the application has never been evaluated for usability. So that the ease of use of the application can not be determined. The study measures the usability of quantitative applications using the System Usability Scale (SUS) method using a 10-item rating scale. Based on the test results, the usability value of general public application users has a